Training critical thinkers in virtual environments: Challenges to autonomy in three universities in Peru, Panama, and the Dominican Republic - Jiménez, Julio; Moreno, Melucipa; Cabrera Félix, Ceferina (Revista Innova Educación, 2026)
In virtual education, student autonomy manifests as operational self-regulation, and critical thinking depends on isolated pedagogical practices, which highlights the need to analyze the pedagogical, technological, and institutional mediations that shape critical autonomy. The objective was to analyze how the formation of critical subjects and autonomy in higher-education virtual environments is configured, based on students’ experiences at three universities in Peru, Panama, and the Dominican Republic. A qualitative approach was adopted, using a multiple and comparative case study design. The purposive and voluntary sample consisted of 18 university students aged 18 to 25, evenly distributed between semi-structured interviews and focus groups, and content analysis of the institutional virtual platform was conducted in each context. The findings show that, across the three cases, operational autonomy predominates, centered on time management and task completion. Critical thinking emerges through debates and real-world cases, although with varying depth, with a technical emphasis in the Peru case, an argumentative emphasis in the Panama case, and a systematic emphasis in the Dominican Republic case. The platforms prioritize administrative functions, which limits reflection. Connectivity and economic inequalities affect all cases, with less impact in the Dominican Republic due to its support policies. It is concluded that the formation of critical subjects in virtual environments is not an automatic result of digitization, but rather depends on pedagogical mediations, institutional decisions, and specific social contexts.